Emerging Trends in the Social and Behavioral Sciences 2015
DOI: 10.1002/9781118900772.etrds0342
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Approaches to Political Science

Abstract: Over the past decade, a growing interest in the possibility that biological factors, including genes, might contribute to individual differences in political and social behaviors has emerged. Behavioral genetic techniques have provided a variety of approaches to quantify the effects of genetic and nongenetic inheritance. However, until quite recently, these methods were largely unknown to political scientists. In this essay, we review the general approaches to modeling genetic and social influences on differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Considering the role of genes and their interplay with the environment is necessary to fully understand the etiology of individual differences in POP, SOP, and PI. In support of this claim, previous studies that investigated genetic and environmental variance components have found evidence for both influences (for overviews, see e.g., [ 18 , 19 ]).…”
Section: Introductionmentioning
confidence: 60%
“…Considering the role of genes and their interplay with the environment is necessary to fully understand the etiology of individual differences in POP, SOP, and PI. In support of this claim, previous studies that investigated genetic and environmental variance components have found evidence for both influences (for overviews, see e.g., [ 18 , 19 ]).…”
Section: Introductionmentioning
confidence: 60%